OPTIMIZATION OF TOTAL CAROTENOIDS, PHENOLIC CONTENT, AND SENSORY ACCEPTABILITY OF JAVA TEA-BASED FUNCTIONAL DRINK ENRICHED WITH RED FRUITS’ OIL EMULSION - Wijaya, Hanny; Natania, Natania; Sonatha, Mei Diana; A'yuni, Qurrata; Caroline, Cindy (Indonesian Journal of Natural Pigments, 2020)
Red fruits’ oil contains 12,000 ppm carotenoid compounds and among them β-karoten was found as the major carotenoid compound. However, the application of red fruits’ oil as the food ingredient is rarely investigated due to its low solubility in aqua-phase, phenolic aroma and bitter aftertaste. Therefore , emulsification of red fruits’ oil in water (oil in water, o/w emulsion) using CMC (carboxymethyl cellulose) as the emulsifier and stabilizer agent considered as alternative to overcome those limitations. In the present work, the optimum concentration of red fruits’ oil emulsion added into Java tea-based functional drink increased the total carotenoid content, gave red color and might enhanced its antioxidant activity. The optimum formula was performed by Response Surface Methodology approach utilizing Design Expert 10.0.7® (DX10) Trial software whereas the emulsion concentration of red fruits’ oil as the variable factor. Red fruits’ oil emulsion which has been prepared from 20% red fruits’ oil and 1.50% CMC as emulsifier and stabilizer was having total carotenoid content of 72.93±1.33 ppm. The optimum concentration of red fruits’ oil emulsion added to Java-tea based functional drink was 5.86%. The addition of red fruits’ oil emulsion increased the total carotenoid content from 0.37±0.13 ppm to5.28±0.05 ppm. The results showed that red fruits’ oil emulsion could be used as red colorant agent in the functional drink while increasing the total carotenoid content, however, reduced the flavor sensory acceptance in high amount